1970
DOI: 10.1083/jcb.47.1.34
|View full text |Cite
|
Sign up to set email alerts
|

Subfractionation of Smooth Microsomes From Rat Liver

Abstract: Total smooth microsomes from rat liver isolated on a Cs+-containing sucrose gradient were concentrated and subsequently fractionated by zone centrifugation on a stabilizing sucrose gradient. The prerequisite for fractionation is to prepare total smooth microsomes in a nonaggregated condition, as well as to utilize a procedure which counteracts enzyme inactivation . The median equilibrium density of the various smooth microsomal vesicles ranges from 1 .10 to 1 .18 . The phospholipid/protein ratio is identical i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
1

Year Published

1973
1973
1992
1992

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(28 citation statements)
references
References 42 publications
1
26
1
Order By: Relevance
“…These results are doubly meaningful, in that they show that the bulk of the microsomal cholesterol is physically independent from the structures bearing group b and ¢ enzymes, and also that the latter structures do not contain appreciable amounts of cholesterol per unit weight, at least in a form accessible to digitonin binding. Our conclusion, which is at variance with the views of other authors (13,23), will be further supported in the next paper of this series (5). The intracellular localization of cholesterol is examined below.…”
Section: Distribution Of Chemical Constituentscontrasting
confidence: 50%
“…These results are doubly meaningful, in that they show that the bulk of the microsomal cholesterol is physically independent from the structures bearing group b and ¢ enzymes, and also that the latter structures do not contain appreciable amounts of cholesterol per unit weight, at least in a form accessible to digitonin binding. Our conclusion, which is at variance with the views of other authors (13,23), will be further supported in the next paper of this series (5). The intracellular localization of cholesterol is examined below.…”
Section: Distribution Of Chemical Constituentscontrasting
confidence: 50%
“…The origin of the two smooth membrane fractions in which the ATPase is concentrated (Table I) is not clear. The lighter of the two fractions may consist of plasma-membranes (9) but whether this is plasmalemma, tonoplast, or both and which way they are folded is not clear. However, it is tempting to suggest that the ATPase is located on the outside of the tonoplast membrane, i.e., the cytoplasmic side of the tonoplast, because it (a) showed specificity for anions (21) and was maximally stimulated by organic anions likely to be accumulated in the vacuole; (b) was saturated at high salt concentration (50 mM) in accordance with the (system 2) ion pump proposed on the tonoplast (14).…”
Section: Discussionmentioning
confidence: 99%
“…The supernatant was then centrifuged at 78,000g (average) for 90 min to sediment the microsomes. Fractionation of the microsomes followed the method of Glauman and Dallner (9). The microsomal pellet was resuspended in 90 ml of 0.25 M sucrose containing 15 mM CsCl, and aliquots of 7 ml were layered over 4.5 ml of 1.3 M sucrose containing 15 mm CsCl.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the question as to whether a given amount of marker enzyme activity is associated with a similar amount of ER membrane has become one of increasing importance (15,25,13,44,32,8) . Several papers have suggested that (a) marker enzymes are heterogeneously distributed on the ER and that (b) "ER marker enzymes" may also be attached to membranes other than those of the ER (15,46,2,18,22,29,24,14,41,39,4,38,30) . The existence of such marker enzyme heterogeneities would be expected to have important consequences when one is interpreting bio-J.…”
Section: Introductionmentioning
confidence: 99%